Exploring the Perceptions and Self-Perceptions of Therapeutic Adherence in Older Adults With Chronic Conditions: A Scoping Review - Alcântara L; Figueiredo T; Costa E (Patient Preference and Adherence, 2025)
Leovaldo Alcântara,1,2 Teodora Figueiredo,3– 5 Elísio Costa3– 5 1Institute of Biomedical Sciences Abel Salazar, University of Porto, Porto, Portugal; 2Department of Education and Psychology, University of Aveiro, Aveiro, Portugal; 3CINTESIS@RISE, Biochemistry Lab, Faculty of Pharmacy, University of Porto, Porto, Portugal; 4Department of Biological Sciences, Faculty of Pharmacy, University of Porto, Porto, Portugal; 5Porto4Ageing—Competences Centre on Active and Healthy Ageing, Faculty of Pharmacy, University of Porto, Porto, PortugalCorrespondence: Elísio Costa, Faculty of Pharmacy, University of Porto, Porto, Portugal, Email emcosta@ff.up.ptAbstract: Few interventions and programmes have proved to be effective in increasing therapeutic adherence. Numerous efforts have been made to identify key factors that significantly influence adherence. In older adults, non-adherence can result from several problems, including insufficient income, lack of health insurance, multimorbidities, polypharmacy, functional disabilities, low medication literacy and demographic factors. However, psychological and psychosocial factors are often neglected in the study of patient-related factors. This scoping review aimed to study the perceptions and self-perceptions that influence all dimensions of therapeutic adherence in older adults with chronic conditions. This scoping review was conducted in accordance with the PCC strategy and following the PRISMA Extension for Scoping Reviews checklist. Three databases (PubMed, Web of Science, and Scopus) were searched from 2014 to the date of the research. In the initial search in the databases, 910 articles were retrieved. After applying the inclusion and exclusion criteria, 15 studies were selected for inclusion. In the selected studies, the factors most consistently associated with perceptions and self-perceptions influencing adherence were: perceived self-efficacy, perception of illness, beliefs about medications, self-perception of physical health status, self-perception of mental health status, perception of social support and perception of ageing. Furthermore, it was identified that there are few studies on patients’ perceptions and self-perceptions related to treatment. The way adherence and related factors were assessed was mainly through the use of self-report scales. Concluding, this scoping review sheds light on the complex factors that influence therapeutic adherence in older adults, emphasizing the role of perceptions and self-perceptions. The psychological and subjective aspects that affect the perceptions and self-perceptions of the older adult population concerning the treatment of chronic diseases have not been deeply studied. Research involving interviews and focus groups with this population can lead to a better understanding of non-adherence and promote effective interventions to increase adherence.Keywords: medication adherence, compliance, gerontology, self-concept, medical plans, patient´s perspectives